An Uigur Decree of Tax Exemption in the Name of Duwa-Khan - Matsui, Dai (Proceedings of the Mongolian Academy of Sciences, 2011)
DOI:http://dx.doi.org/10.5564/pmas.v0i4.41 Proceedings of the Mongolian Academy of Sciences 2007 No 4 pp.60-68